Neurocutaneous Syndromes and the Neural Crest - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The role of the neural crest as an inducer of neurocutaneous syndromes and associated craniofacial abnormalities is proposed by researchers at the University of Calgary and Alberta Children's Hospital, AB, Canada.